2010
DOI: 10.1007/s00392-010-0260-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary versus intravenous bolus abciximab application in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention: 6-month effects on infarct size and left ventricular function

Abstract: Intracoronary abciximab application in STEMI patients undergoing PCI is superior to standard IV treatment with respect to infarct size, recovery of LV function and reverse remodelling 6 months after infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
1
23
2
Order By: Relevance
“…Thus, we can be confidant that IC GP IIb/IIIa inhibitor delivery results in improved LVEF 6 months after MI, and this improvement appears to be maintained at 12 months. However, in contrast to our findings, Eitel et al [25] reported no improvement in LVEF if patients were given IV abciximab. This observation by Eitel's group is also at odds against the finding reported by Neumann et al [24] as we discussed earlier.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, we can be confidant that IC GP IIb/IIIa inhibitor delivery results in improved LVEF 6 months after MI, and this improvement appears to be maintained at 12 months. However, in contrast to our findings, Eitel et al [25] reported no improvement in LVEF if patients were given IV abciximab. This observation by Eitel's group is also at odds against the finding reported by Neumann et al [24] as we discussed earlier.…”
Section: Discussioncontrasting
confidence: 99%
“…Neither IV or IC approach altered the patients' E/E' following primary PCI at 1 year. Second, our longer duration of follow-up of 1 year may have explained some of the differences between our study and that of Eitel et al [25]. We do not have interim 6 months follow-up data for comparison.…”
Section: Ic Bolus (N = 31)mentioning
confidence: 63%
See 2 more Smart Citations
“…However, to achieve these favorable effects, it is advisable to administer intracoronary abciximab bolus after thrombus penetration by the PCI guidewire, and when the risk of bleeding is an issue, intracoronary bolus of GPI and no infusion strategy may be useful. Some small studies showed infarct size reduction, decrease in microvascular obstruction, improvement in the LVEF, and improvement in myocardial blush, but no significant difference in the clinical outcomes with intracoronary bolus admnistration of abciximab, with and without subsequent infusion [62][63][64][65] . However, meta-analyses published recently, demontrated not only a favorable effect of intracoronary bolus on TIMI flow, but also on target vessel revascularization and short-term mortality after PCI with no increase of bleeding complications [66,67] .…”
Section: Pharmacologic Agentsmentioning
confidence: 99%